2020
DOI: 10.1186/s13014-020-1464-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal radiotherapy for patients with internal mammary lymph node metastasis from breast cancer

Abstract: Background: This study aimed to determine the optimal radiotherapy (RT) regimen for patients with clinical metastasis to the internal mammary lymph node (cIMN+) from breast cancer. Methods: We retrospectively reviewed the medical records of 84 patients with cIMN+ breast cancer treated with curative surgery, taxane-based chemotherapy, and postoperative RT between January 2009 and December 2014. Postoperative RT was administered to the whole breast or chest wall using 50 Gy in 2 Gy fractions. Boost RT to the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The only feasible treatment for residual IMN metastasis is IMN-RT. In their study, Yang et al concluded that the IMN-RT was particularly suitable for patients with larger IMN (17). In their study, Aleknavičius et al found that IMN-RT was correlated with a better survival outcome for patients with moderate-risk disease (stage T1-2N1), and showed no association for better survival for high-risk disease (stage T3-4N2-3) (18).…”
Section: Discussionmentioning
confidence: 98%
“…The only feasible treatment for residual IMN metastasis is IMN-RT. In their study, Yang et al concluded that the IMN-RT was particularly suitable for patients with larger IMN (17). In their study, Aleknavičius et al found that IMN-RT was correlated with a better survival outcome for patients with moderate-risk disease (stage T1-2N1), and showed no association for better survival for high-risk disease (stage T3-4N2-3) (18).…”
Section: Discussionmentioning
confidence: 98%
“…Further, IMNþ was mostly determined by radiologic examinations; only 2%e57% of the participants were diagnosed with IMN þ by both radiologic findings and histopathologic evaluation of the IMN. In addition, a radiation dose of 45.0e66.5 Gy was administered to the IMN chains, and the amount of IMN radiation dose was determined at the discretion of the physician [8,11,12,14] or the IMN response to NAC [26]. In a study by Zhang et al a dose of 66 Gy was prescribed to the IMN region in patients with residual radiographic IMN adenopathy after NAC, while and IMN dose of 60 Gy was given to patients showing complete radiologic response after NAC [26].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the study of Park et al another study showed a significant association between IMN radiation dose and breast cancer survival. In a study by Yang et al the DFS was significantly influenced by the IMN dose in patients with large IMN adenopathy (!1 cm) [8]. The 5-year DFS in patients receiving a high IMN EQD2 (!63.6 Gy) and low IMN EQD2 (<63.6 Gy) was 69.3% and 33.3%, respectively (p < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of reducing the PTV margin, reduction of the prescribed to 45 Gy for the IMN can be discussed in patients with lower risk factors. For patients with IMN positive lymph nodes, however, there is emerging evidence that IMN irradiation with higher doses (IMNI ≥ 63.6 Gy or boost-RT to metastases) is associated with a better DFS compared to lower doses (50.0–63.5 Gy) and excellent IMN control [ 33 ]. This emphasizes the particular importance of adequate dose coverage and sufficient PTV-margins in these patients.…”
Section: Discussionmentioning
confidence: 99%